O olhar do professor do ensino fundamental e médio sobre o texto escrito pelo surdo - Santos, Conceição Maria Marinho dos (2009)
This work spook about the conception of teacher in educational context incluse about of writing text deaf student. Of general way in formation of that docent, the teaching of language Portuguese to deaf is not treatise and that cause difficulties in understanding of element that compose the text of that apprentice, generally, cross by signal of language. Of that way the teacher does not understand the reason of performance of deaf. The teacher does not identify. The element that can be present in text in writing text, and that compose the transition of a language to other, the teacher reconhecem how error. Use a quantitative methodology, descriptive and participaram its eleven subjects. The collect of information was categorizada. Seguindo-se its analysis. The sintatica construction use by deaf reveal the influence of language of signal that, by present other structure, bring peculiarity to the writing of second language, and in thiscan compromise the understanding of text, when it s read by teacher that do not understand it. The information took us to reflection that the point to the fact that the teacher of special classroom in spite of have a education specialized they do not get improve the writing of deaf student, such whom the student of inclusive classroom what let us suggest to teacher a review of theirs practice that it should include the perspective designate to conceive that treat it of a apprentice of a second language, independent of auditive loss that the deaf student has